Implementing Audio-Visual Folktales with Blooket-Based Gamification in Listening Instruction: A Descriptive Study of High School Students - Eka Sartika; Salam; Wa Ode Irawati (International Journal of Educational Practice and Policy, 2026)
This study describes the implementation of an audio-visual folktale, combined with Blooket-based gamification, in the listening instruction of tenth-grade students at SMA Negeri 6 Gorontalo, Indonesia. A qualitative descriptive design was employed, involving 20 students as research participants. Data were collected through classroom observation, semi-structured interviews with seven students, and documentation, and were analyzed using an interactive qualitative analysis model comprising data reduction, data display, and conclusion drawing/verification. The learning process integrated the local folktale Hulontalangi, presented in audio-visual form via YouTube, with a 10-item multiple-choice comprehension activity delivered through the Blooket platform. The findings describe how students engaged with the medium, the range of scores and accuracy they achieved on the gamified comprehension task (mean accuracy 83%, with 18 of 20 students reaching at least 70% accuracy), and the perceptions and challenges they reported in interviews. Students generally described the experience as more enjoyable and interactive than conventional listening instruction, while also reporting technical constraints related to internet connectivity. As a qualitative descriptive study, these findings characterize the implementation and students' responses to it rather than establishing a causal effect on listening achievement; they suggest that audio-visual folklore combined with Blooket-based gamification is a feasible and well-received instructional approach worth further, more controlled investigation.